Acute severe hepatitis of unknown etiology in children: A mini-review - Andri Frediansyah; Amanda Yufika; Khan Sharun; Muhammad Iqhrammullah; Deepak Chandran; Sukamto S. Mamada; Dina E. Sallam; Yousef Khader; Yohannes K. Lemu; Fauzi Yusuf; James-Paul Kretchy; Ziad Abdeen; J. Smith Torres-Roman; Yogesh Acharya; Anastasia Bondarenko; Aamer Ikram; Kurnia F. Jamil; Katarzyna Kotfis; Ai Koyanagi; Lee Smith; Dewi Megawati; Marius Rademaker; Talha B. Emran; Ziad A. Memish; Sandro Vento; Firzan Nainu; Malik Sallam; Harapan Harapan (Narra J, 2022)
The emergence of acute, severe non hepA–E hepatitis of unknown etiology (ASHUE) has attracted global concern owing to the very young age of the patients and its unknown etiology. Although this condition has been linked to several possible causes, including viral infection, drugs and/or toxin exposure, the exact cause remains unknown; this makes treatment recommendation very difficult. In this review, we summarize recent updates on the clinical manifestations, complemented with laboratory results, case numbers with the global distribution and other epidemiological characteristics, and the possible etiologies. We also provide the proposed actions that could be undertaken to control and prevent further spread of this hepatitis. Since many etiological and pathological aspects of the acute non hepA–E hepatitis remain unclear, further research is needed to minimize the severe impact of this disease.